DIGITAL TRANSFORMATION OF MICRO, SMALL, AND MEDIUMENTERPRISES (MSMES) DURING THE PANDEMIC: CHALLENGES AND STRATEGIES - Era Purike; Iyad Abdallah Al- Shreifeen; Mohammad Taqiuddin Mohamad (INJOSEDU: International Journal of Social and Education, 2025)
Digital transformation of Micro, Small and Medium Enterprises (MSMEs) during the pandemic has become a vital step to ensure business survival and growth. The COVID- 19 pandemic has accelerated the need for digital technology adoption due to physical restrictions that reduce face-to-face interactions. While this offers various opportunities such as market expansion and improved operational efficiency, MSMEs also face various challenges, including financial limitations, low digital literacy, and uneven internet infrastructure and connectivity. To overcome these challenges, a comprehensive strategy is needed, including improved digital literacy, utilisation of digital platforms, and collaboration with external parties. Digital transformation is not only a short-term solution during the pandemic, but also a long-term strategy to improve the competitiveness and sustainability of MSMEs in facing the industrial era 4.0. With the right support from the government and other stakeholders, MSMEs can continue to grow and contribute significantly to the economy.